2012
DOI: 10.1063/1.4768532
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Bi-concentration dependence of the bandgap and spin-orbit splitting in InGaBiAs/InP semiconductors for mid-infrared applications

Abstract: Replacing small amounts of As with Bi in InGaBiAs/InP induces large decreases and increases in the bandgap, E, and spin-orbit splitting, Δ, respectively. The possibility of achieving Δ > E and a reduced temperature (T) dependence for E are significant for suppressing recombination losses and improving performance in mid-infrared photonic devices. We measure E (x, T) and Δ (x, T) in InGa BiAs/InP samples for 0 x 0.039 by various complementary optical spectroscopic techniques. While we find no clear evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…The strain of InGaAsBi is also calculated and can be designed with zero or a small strain depending on In and Bi concentrations. Furthermore, they studied optical properties of In 0.53 Ga 0.47 Bi x As 1−x /InP samples for x ≤ 3.2% [64,178]. The PR results resolve clear Eg and Eg + ∆ SO features, with Eg ≈ ∆ SO near x = 3.2% at RT.…”
Section: Telecom and Mir Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…The strain of InGaAsBi is also calculated and can be designed with zero or a small strain depending on In and Bi concentrations. Furthermore, they studied optical properties of In 0.53 Ga 0.47 Bi x As 1−x /InP samples for x ≤ 3.2% [64,178]. The PR results resolve clear Eg and Eg + ∆ SO features, with Eg ≈ ∆ SO near x = 3.2% at RT.…”
Section: Telecom and Mir Lasersmentioning
confidence: 99%
“…In addition, by adjusting the x, y compositions, one can obtain the desired bandgap suitable for device application and lattice matched to InP substrate at the same time. A theoretical cutoff wavelength of InGaAsBi is predicted to reach as long as 6 µm, further extending the wavelength to the mid-IR regime [64].…”
Section: Ingaasbimentioning
confidence: 99%
See 1 more Smart Citation
“…Since replacing As by N and Bi in GaAs introduces, respectively, tensile and compressive strain, the N and Bi compositions in GaBi x N y As 1− − x y can be chosen to lattice-match the alloy to a GaAs substrate, while allowing access to the 1.3 μm and 1.5 μm wavelength ranges and beyond. Theoretical calculations have shown that GaBi x N y As 1− − x y retains the large upward bowing of [43,44] the spin-orbit-splitting energy present in GaBi x As 1−x [20]. Because co-alloying Bi with N causes a giant reduction in the band gap, this offers the possibility to eliminate the CHSH Auger recombination mechanism in lasers operating across a wide wavelength range, from 1.5 μm through mid-infrared wavelengths [45].…”
Section: Tight-binding and K · P Models For The Electronicmentioning
confidence: 96%
“…Hamiltonians. Note that the band labels refer to the character of each band at k = 0; these labels do not retain their meaning at finite k when bands start to mix k · p model, compared to optical absorption, PR and photo-luminescence (PL) measurements of the samples discussed in [42][43][44]. Overall, we note the excellent agreement between the calculated and measured values of E g and of Δ SO for the different compositions, confirming that the 12-band k · p model provides an accurate description of the valence band structure of dilute bismide alloys.…”
Section: Application Of the 12-band Model To Gabi X As 1−xmentioning
confidence: 99%